1993
DOI: 10.1300/j043v07n02_08
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Patient Satisfaction

Abstract: This paper investigates the correlates, dimensionality, and determinants of patient satisfaction in the hospital health care encounter. All of the individual hospital characteristics assessed were found to be significantly related to patient satisfaction. The findings suggest that patients evaluate hospital service quality along four distinct dimensions. The relative importance of these four factors in predicting overall satisfaction, in descending order, is: (1) physician/capabilities, (2) nurses/staff, (3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Respondents reported good results with the care provided from the professionals, with scores above four points, but the amenities were rated below this score. The present findings seem to be consistent with another study 7 , which found the following factors to be scored, in descending order: medical performance, nursing staff, amenities and accessibility. In another study in Israel 8 , the attitudes of nurses and medical care were the most important determinants of patient satisfaction with the care received.…”
Section: Discussionsupporting
confidence: 93%
“…Respondents reported good results with the care provided from the professionals, with scores above four points, but the amenities were rated below this score. The present findings seem to be consistent with another study 7 , which found the following factors to be scored, in descending order: medical performance, nursing staff, amenities and accessibility. In another study in Israel 8 , the attitudes of nurses and medical care were the most important determinants of patient satisfaction with the care received.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals not recruited and not followed up differed significantly from those included in the analysis in age, gender, and level of health, all characteristics that have been shown to be significantly related to satisfaction and communication ratings. The bias in the sample, that patients not followed up in the one‐month survey were more likely to have public assistance for medical coverage and to be male and African American, may artifactually raise our estimation of patient's ratings of their attending physicians' communication behaviors, given that the last two characteristics are associated with lower ratings of physician communication behaviors (Hall, Elliott, and Stiles 1993). However, the response rate in our sample of eligible discharged patients of 75 percent is similar to the typical response rates for hospital satisfaction surveys (Sitzia and Wood 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing care, report of pain while in the hospital, level of health, race, age, gender, socioeconomic level have all been shown to affect patient's ratings of the care they receive in the hospital (Hall, Elliott, and Stiles 1993). To control for these variables, we asked patients during the 1‐month follow‐up survey to rate whether they had confidence and trust in the nurses treating them on a three‐point scale: Yes, always; Yes, sometimes; No, never.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient satisfaction adapted from Tucker and Adams [46], was measured using 9 items, and a sample item is I have easy access to a medical specialist I need. Medical equipment (ME) comprised of 4 items with the sample item the use of up-to date medical equipment is well managed [47]. Information received (IR) included 4 items, and distance from hospital (DFH) included 3 items from Thi, et al [48].…”
Section: Methodsmentioning
confidence: 99%